1988
DOI: 10.1073/pnas.85.13.4919
|View full text |Cite
|
Sign up to set email alerts
|

Purification and subunit structure of a putative K+-channel protein identified by its binding properties for dendrotoxin I.

Abstract: The binding protein for the K+-channel toxin dendrotoxin I was purified from a detergent extract ofrat brain membranes. The purification procedure utilized chromatography on DEAE-Trisacryl, affinity chromatography on a dendrotoxin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(68 citation statements)
references
References 30 publications
(29 reference statements)
2
66
0
Order By: Relevance
“…In addition, Sh proteins may undergo posttranslational modifications such as glycosylation and phosphorylation, which could change the properties of Sh channels . Channels composed of Sh subunits can apparently also interact with other not yet identified subunits, and this may also change the functional properties of the final product (Rehm et al, 1989a,b;Rehm and Lazdunski 1988;Rudy et al, 1988Rudy et al, , 1991. Factors such as those listed here are likely to contribute to the functional properties of native channels containing HKShIIIC proteins.…”
Section: Chromosomal Mappingmentioning
confidence: 87%
“…In addition, Sh proteins may undergo posttranslational modifications such as glycosylation and phosphorylation, which could change the properties of Sh channels . Channels composed of Sh subunits can apparently also interact with other not yet identified subunits, and this may also change the functional properties of the final product (Rehm et al, 1989a,b;Rehm and Lazdunski 1988;Rudy et al, 1988Rudy et al, , 1991. Factors such as those listed here are likely to contribute to the functional properties of native channels containing HKShIIIC proteins.…”
Section: Chromosomal Mappingmentioning
confidence: 87%
“…Toxins play an important role in the molecular characterization of potassium channels (Rehm & Lazdunski, 1988;Scott et al, 1990;Garcia-Calvo et al, 1991), which is complementary to cDNA cloning approaches. The discovery and characterization of novel toxins which selectively modulate different channel subtypes will no doubt continue to contribute to our understanding of structural and functional relationships between different members of this large family of ion channel proteins.…”
Section: A23187 (Results Not Shown)mentioning
confidence: 99%
“…These peptides comprise 57-60 aa and three disulfide bonds that stabilize a "Kunitz-type toxin" fold. Initially, the high affinity binding of dendrotoxins was exploited to isolate a K ϩ channel protein (24). Later, structure-activity studies of ␣-and ␦-dendrotoxins revealed the importance of the functional dyad, and several models of the interaction of dendrotoxins with K ϩ channels have been proposed (25,26).…”
Section: Potassium Channel Toxinsmentioning
confidence: 99%